Importance of Hepcidin in the Etiopathogenesis of Anemia in Inflammatory Bowel Disease - Karaskova, Eva; Pospisilova, Dagmar; Velganova-Veghova, Maria; Geryk, Milos; Volejnikova, Jana; Holub, Dusan; Hajduch, Marian (Digestive diseases and sciences, 2021)
Anemia is the most common extraintestinal systemic complication of inflammatory bowel disease. Iron deficiency anemia and anemia of chronic disease are among the most frequent types. Intestinal iron absorption is controlled by the activity of ferroportin. Cells with high expression of ferroportin include enterocytes, and also macrophages and hepatocytes. Iron homeostasis is controlled by the hepcidin-ferroportin axis. Hepcidin is a central regulator of iron metabolism and can also serve as a marker of systemic inflammation. During systemic inflammatory response, the synthesis of hepcidin increases, and hepcidin binds to ferroportin and inhibits its activity. Thus, iron is not absorbed from the bowel into the circulation and also remains sequestered in macrophages. Conversely, hepcidin synthesis is suppressed during conditions requiring increased iron intake for enhanced erythropoiesis, such as iron deficiency anemia or hypoxia. Here, ferroportin is not blocked, and iron is actively absorbed into the bloodstream and also released from the stores. Production of hepcidin is influenced by the status of total body iron stores, systemic inflammatory activity and erythropoietic activity. Oral iron therapy is limited in inflammatory bowel diseases due to ongoing gastrointestinal inflammation. It is less effective and may worsen the underlying disease. Therefore, the choice between oral and parenteral iron therapy must be made with caution. Oral iron would be ineffective at high hepcidin levels due to concurrent ferroportin blockage. Contrarily, low levels of hepcidin indicate that oral iron therapy should be successful. An understanding of hepcidin can help in understanding the body's reaction to iron depletion during the inflammatory process.
Keywords: železo; Hepcidins; hepcidiny; proteiny přenášející kationty; idiopatické střevní záněty; Gene Expression Regulation; Anemia; Humans; lidé; Cation Transport Proteins; Inflammatory Bowel Diseases; Iron; regulace genové exprese; anemie